Aromatase reduces sperm motility by down-regulating the expression of proteins related to ATP synthesis in seminal plasma extracellular vesicles - Xuliang Luo; Yan Guo; Xuelian Li; Zi Mei; Haobo Zhou; Ping Qiu; Haoxin Wang; Yan Chen; Yanzhang Gong (BMC Genomics)
Abstract Background Aromatase, encoded by Cyp19a1, is the rate limiting enzyme in biosynthesis of estrogens, and excessive aromatase can reduce the semen quality in roosters. Seminal plasma extracellular vesicles (SPEV) are nanoscale vesicles that carry and transmit signaling molecules, thereby affecting semen quality. Currently it is still unclear whether SPEV are involved in the process of that aromatase affects the quality semen in chicken. To clarify this issue, lentivirus carrying Cyp19a1 (LV-CYP19A1) for over-expression of aromatase was constructed and injected to testis of 35-week-old roosters. Semen quality and seminal plasma hormone were measured, and SPEV were also extracted and proteome sequencing was performed after treatment of LV-CYP19A1. Results The results indicated that semen volume, fertility, sperm motility, testosterone (T) levels were significantly decreased, and estradiol (E2) levels were significantly increased in LV-CYP19A1 group than those in control group (P < 0.05). Through proteomic analysis of SPEV, we identified 966 differentially expressed proteins (DEPs) in the comparison of LV-CYP19A1 group and control group. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) items of DEPs are mainly enriched in ATP synthesis coupled electron transport, flagellated sperm motility, regulation of steroid biosynthetic process, and PI3K-Akt signaling pathway. Furthermore, 8 proteins including ENO4, APOB, SDHA, SDHB, UQCRC1, VIN, PITGB3 and FXN were identified as key proteins in SPEV involving in the process of aromatase regulated rooster semen quality. Conclusions Our results reveal that aromatase can down-regulate the protein expression related to regulation of ATP synthesis and metabolism, and sperm motility in SPEV, thereby reducing semen quality in roosters.